Incidence of Yersina enterocolitica in sheep in the south region of Iraq - Abdul Hussein Saleh, Ban; Zenad, Mohammed M. (The Iraqi Journal of Veterinary Medicine, 2018)
Yersiniosis is a zoonotic disease which infects many animal species. A preliminary study was done to detect the incidence of Yersinia enterocolitica in sheep. One thousand and two hundred fecal samples were collected randomly from sheep in four governorates in the southern region of Iraq: Thi-Qar, Al-Muthana, Messan and Basrah, in the period from July 2016 to June-2017. Enrichment Yersinia broth at 4°C for 48 hours was used for isolation of Yersinia enterocolitica. Selective Cefsulodin Irgasan Novobiocin and non selective media were used for bacterial culture. The identification of Yersinia enterocolitica was based on colony morphology and biochemical characters, API 20E and VITEK2 compact systems were used for the same purpose also. Data were analyzed by using SAS, Version 9-1. Chi- square test was used for comparison. The total isolation rate of Y. enterocolitica was 5.16% (62). High and low rates of isolation were recorded in Al-Muthana (6. 01%) and Basrah (3.86%). Similarly a significant high isolation rate was recorded in diarrheic sheep (17.4%), moreover the infection rate increased significantly (9.5%) in the young sheep (1day to 6 month's age). Furthermore, the recovery rate of Y. enterocolitica increased significantly during the cold months (12%) as compared with temperate and hot months (spring and summer), at the same instance, non significant variation among sex difference was detected. Fever, diarrhea and mild to moderate degree of dehydration were the most common clinical manifestations observed on the infected animals. Conclusively sheep were considered a source of infection to other species including human being, and the spread of microorganism increased markedly in the cold and wet environment.